STUDI EFEK DISGLIKEMIA PADA PENGGUNAAN INJEKSI CIPROFLOXACIN DAN LEVOFLOXACIN DENGAN KOMBINASI ANTIDIABETIK ORAL DAN INSULIN PADA PASIEN DIABETES MELITUS DI INSTALASI RAWAT INAP RSUD LASINRANG, PINRANG, SULAWESI SELATAN - Ririn Sutanti Abdul; Marianti A Manggau; Agus Alim Abdullah (Faculty of Pharmacy, Hasanuddin University, 2020)
This study was aimed to determine the dysglycemia effects of fluoroquinolone antibiotics, namely ciprofloxacin or levofloxacin in hospitalized diabetes melitus patients who also taking oral antidiabetic or insulin in Lasinrang Hospital Pinrang by measuring blood glucose levels value before and after using fluoroquinolon. The research was conducted by a non-experimental observational study with a descriptive-analytic design. Sampling was done by retrospectively method and 49 samples were obtained that met the inclusion and exclusion criteria. The results of this study showed no hypoglycemia effect in hospitalized diabetes melitus patients, who was taking ciprofloxacin or levofloxacin. The percentage effect of hyperglycemia that occurs in patient using ciprofloxacin was 34.78% and levofloxacin was 30.77%. Based on statistical tests, blood glucose levels before and after the patients with diabetes mellitus taking ciprofloxacin or levofloxacin injection showed a significant difference.